Evaluation of Primary Immunization Coverage in an Industrial City of Uttar Pradesh - Chaturvedi R; Sharma RP; Martolia DS; Nigam S; Varma P; Midha T (Online Journal of Health & Allied Sciences, 2015)
Background: There is gradual albeit a slow progress in the performance of routine immunization in India over last few years. Six states with high population contribute to 80% of 8.1 million unimmunized children in the country out of which 52% of the total unimmunized reside in Uttar Pradesh and Bihar alone. Objectives :1. To study the primary immunization coverage of children aged 12-23 months in the slums of Kanpur Nagar 2.To calculate drop out rate for various vaccines. Methodology: 30 cluster sampling technique. Results: 52.38% study subjects were fully immunized, 29.52% were partially immunized and 18.10% were not immunized at all. Coverage was highest for BCG vaccine (81.90%) and lowest for Hepatitis B3(41.90%). Drop out rate for DPT / OPV (I-III), DPTI – Measles and BCG – Measles was 25.88%, 34.70% and 35.46% respectively. Conclusion: Sustained efforts are required to achieve the target of universal coverage of immunization in children.